Management and Evaluation as a confluence (2011)
Management and evaluation had from primitive times always converge at some point in the decision-making process and never to be separated until they compositely terminate at the realization of the objective, which they were set out to achieve. A careful analysis of the management process, which is principally decision-making and execution of the import of such a decision, reveals that evaluation is inherently in-built in the management process. No effective management can take place if the process fails to take cognizance of evaluation as its majof tool. The main objective of the process is organizational/ institutional effectiveness ensuing from its responsiveness, which is informed by the in-built evaluation mechanism in the management process. Therefore, the import of this paper was the examination of the management process is- a -vis the evaluation mechanism it utilizes to achieve its objective as well as discuss their interrelating roles, where divergence and convergence occur and the terminal of both processes after they had converged. It must be noted that organizational/ institutional objective berth the management process and the desire to effecively achieve these objectives with little or no deviation is the driving force for inclusion of evaluation as an indispensible element of the process. Concergence occurs the moment the need for evaluation of the process is realized. The paper concluded that they both converge even though they individually begun thier journeys at different points hitherto and then continue together both terminating as one entity at the point when organizational goal is achieved